Thirsty? Choose Water! Behavioural interventions and water stations in secondary schools a two-by-two factorial randomised controlled trial - Nicole Kajons; Michael David; Justine Gowland-Ella; Peter Lewis; Samantha Batchelor (BMC, 2018)
Abstract Background Childhood overweight and obesity is a significant public health issue. A key contributing factor is sugar sweetened beverages (SSBs) consumption. Evidence suggests that secondary school students are frequent consumers of SSBs, with high daily consumption. The promotion of water consumption and provision of chilled water stations can reduce SSBs consumption. The Thirsty Choose Water! study will evaluate the effectiveness of two interventions, a behavioural intervention, Thirsty? Choose Water! behavioural intervention (TCW-BI), that target students through the domains of the health promoting high schools framework, and the second intervention is the installation and promotion of chilled water stations. Methods/design This community trial will recruit 60 secondary schools from across three Local Health Districts (LHDs) within New South Wales (NSW). A two-by-two factorial study design will be used to determine the effect of the Thirsty? Choose Water! behavioural intervention (TCW-BI), and the installation of chilled water stations. The recruited secondary schools will be randomised and non-blinded to one of four study arms receiving either the TCW-BI or chilled water stations, both interventions, or neither (control group). Baseline measures will be collected including student self-report surveys which will gather data regarding knowledge, attitudes and consumption of water and SSBs, a school profile and an environmental scan. Student surveys will be repeated post the intervention and at follow-up. Regular water meter readings will determine the water flow from the chilled water stations across the study period. Discussion There is an increasing body of evidence which suggests that decreasing consumption of SSBs can impact positively on childhood overweight and obesity. However, in the Australian context there are limited studies on how this may occur in the secondary school setting. This study will add to this evidence base and establish the effectiveness of TCW-BI and chilled water stations, either alone or combination on increasing water consumption in adolescents. Information about barriers and facilitators to implementation will be documented. Packages to support the implementation of the TCW-BI as a state-wide initiative will be developed. Trial registration Australian and New Zealand Clinical Trials Register ACTRN12618000526279 April 2018.